The Bureaucratic Trap of Flexibility: A Critical Policy Analysis on The Homogenization of Final Assignment Forms In PTKIN Guidebooks - Dani Hermawan (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study examines how State Islamic Higher Education Institutions (PTKIN) in Indonesia interpret the policy on diversified final assignments as regulated in Article 18, paragraph 9, of Permendikti Saintek No. 39 of 2025 concerning the National Standards of Higher Education. The study was undertaken because the policy’s flexible intention may become rigid and bureaucratic when translated into institutional guidebooks. The main argument is that diversification should not only expand the forms of student final assignments, but also transform the assessment logic used to evaluate them. This study employed a qualitative approach using Critical Policy Analysis (CPA). Data were collected through document analysis of academic guidebooks from three PTKINs: UIN Khas Jember, UIN Maulana Malik Ibrahim Malang, and UIN Satu Tulungagung. The analysis focused on how prototypes, projects, and product-based final assignments are defined, structured, and assessed within each institutional document The findings reveal a tendency toward structural and methodological homogenization in the institutional translation of diversified final assignments. The guidebooks formally recognize prototypes and projects, yet often require them to follow thesis-like structures. The most explicit case appears in the 2025 guidebook of UIN Khas Jember, which equates prototypes and projects with Research and Development (R&D) design and requires a rigid multi-stage validation process. This creates a double burden and methodological misalignment because students must adjust practical and creative outputs to theoretical research frameworks that may not fit the nature of their work This study implies that PTKINs need to develop more flexible, output-oriented, and differentiated assessment guidelines that align with the spirit of Permendikti Saintek No. 39 of 2025. However, the study is limited to document analysis of three PTKINs, so further research should examine implementation practices across broader institutional contexts.